The Influence of Digital Literacy and Information Technology Development on Human Resources Quality Mediated by Reading Interests - Marianus Euricho Gutero; Syamsul Hadi; Mohammad Ahyar Syafwan Lysander (SMARTINDO, 2025)
Purpose - This study aims to examine the influence of Digital Literacy and Information Technology Development on the Quality of Human Resources (HR) of students of the Faculty of Economics, Sarjanawiyata University Tamansiswa Yogyakarta, with Reading Interest as a mediating variable. Design/methodology/approach - The approach used in this study is quantitative with a survey method. The research sample consisted of 95 students selected using the simple random sampling technique. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through the assistance of the SmartPLS application. Originality - This study contributes to understanding the relationship between digital literacy, information technology development, and the quality of human resources in the context of higher education, by considering the mediating role of reading interest. Findings and Discussion - The results of the study indicate that Digital Literacy and Information Technology Development have a positive and significant effect on Human Resource Quality. However, Digital Literacy does not show a significant effect on Reading Interest. In addition, Reading Interest also does not have a significant effect on Human Resource Quality, and does not mediate the relationship between Digital Literacy and Information Technology Development on Human Resource Quality. Conclusion - These findings indicate that improving the quality of human resources does not solely depend on strengthening digital literacy and information technology, but also requires supporting strategies such as strengthening practical skills and innovation in learning methods.